Translational and Personalized Medicine - Pavelić, Krešimir; Martinović, Tamara; Pavelić Sandra Kraljević (Medicine, Law & Society, 2015)
The idea behind personalized medicine is to tailor health care to an individual’s unique genetic makeup. Hitherto, “one size fits all” approach was used in medicine. With the rise of personal medicine, we are moving towards a more precise, predictable and powerful medicine that is customized for each individual patient. To allow for an improvement in the acceleration and efficacy of drug development, high-throughput methods (“omics”) are rapidly being developed. This leads to understanding of multiple factors that are involved in disease progress on an individual level. In order to analyze the great amount of data that is collected from such experiments, one has to turn to systems biology, an interdisciplinary science that studies complex interactions within a biological system. Finally, translational medicine comes into play, by “translating” the information gathered from research into diagnostic tools, medicines and policies, with the final goal of improving individuals’ health. Personalized medicine is one of the future, and it will revolutionize the current practice of diagnosis-based medicine, once fully developed.